2011
DOI: 10.1002/mnfr.201100436
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of olive oil phenolic compounds in rat tissues after administration of a phenolic extract from olive cake

Abstract: After a single ingestion of olive oil phenolic compounds, these were absorbed, metabolized and distributed through the blood stream to practically all parts of the body, even across the blood-brain barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
128
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(141 citation statements)
references
References 45 publications
9
128
3
1
Order By: Relevance
“…It has been shown that after an acute ingestion of olive phenolic compounds, they are absorbed, metabolized, and distributed though the blood stream to practically all parts of the body, even across the blood-brain barrier. 24 Free forms of certain phenolic compounds were determined in certain tissues, that is, oleuropein in the plasma and brain, luteolin in the kidney, testicle, brain, and heart, or hydroxytyrosol in the plasma, kidney, and testicle, but plasma mainly contained the metabolites. Using the Caco-2/TC7 cells as a model of the human intestinal epithelium, limited metabolism of olive oil phenolics was observed; the methylated conjugates were the major metabolites detected.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that after an acute ingestion of olive phenolic compounds, they are absorbed, metabolized, and distributed though the blood stream to practically all parts of the body, even across the blood-brain barrier. 24 Free forms of certain phenolic compounds were determined in certain tissues, that is, oleuropein in the plasma and brain, luteolin in the kidney, testicle, brain, and heart, or hydroxytyrosol in the plasma, kidney, and testicle, but plasma mainly contained the metabolites. Using the Caco-2/TC7 cells as a model of the human intestinal epithelium, limited metabolism of olive oil phenolics was observed; the methylated conjugates were the major metabolites detected.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies based on metabolite-profiling approaches demonstrated that oleuropein is rapidly absorbed and distributed through the blood stream to various tissues in vivo (Serra et al 2012) and entered to cell cytoplasm in vitro (Quirantes-Pine et al 2013). In acute toxicity studies for oleuropein, no adverse effects were observed in mice at doses as high as 1 g/kg of body weight (Petkov and Manolov 1972).…”
Section: Discussionmentioning
confidence: 99%
“…In acute toxicity studies for oleuropein, no adverse effects were observed in mice at doses as high as 1 g/kg of body weight (Petkov and Manolov 1972). Taking into account concentration at which PPARc inhibition was detected in vitro (200 lM) and reported level of oleuropein (C max 4 h: 24 lM) in rat plasma (Serra et al 2012) after an acute intake of a phenolic extract from olive cake (3 g/kg body weight, oleuropein content *0.1 mg/g of extract), oleuropein could potentially modulate PPARc activity also in vivo, which needs to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…We used a previously validated technique (Serra et al, 2012), specifically looking for OLE and its main metabolites, hydroxytyrosol (HT), and homovanillic acid (HVA). The mice were sacrificed by cervical dislocation, and the brains were rapidly removed and snap-frozen.…”
Section: Liquid Chromatographyemass Spectrometry/mass Spectrometry Anmentioning
confidence: 99%
“…3.7. Brain concentrations of OLE, HT, and HVA after an acute administration of OLE in wt mice It is known that intestinal OLE is rapidly adsorbed in the plasma of both rats and humans, distributed to various tissues, including brain, conjugated and metabolized in a number of compounds including HT, HVA and elenolic acid, and excreted in the urine (De Bock et al, 2013;Serra et al, 2012). We therefore sought to quantify by liquid chromatographyemass spectrometry/mass spectrometry (LC-MS/MS) the concentrations of OLE and its major metabolites HT and HVA in the brains of OLE-administered mice.…”
Section: Ole Rescues Hfs-induced Ltp In Aged Tgcrnd8 Hippocampal Slicesmentioning
confidence: 99%